Divinidades y devotos indígenas en la Tarraconensis: las dedicaciones colectivas (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper focuses on the votiv inscriptions of the provincia Tarraconensis that mention gods or dedicants with indigenous names, considering their historical context —the civitas—, the diverse information given by the texts, and their public or private nature. Some of the most problematic documents are also discussed and revised.
Keywords: Epigraphy; Indigenous religion and anthroponimy; Ciuitas; Tarraconensis